CpG-ODN + IFN-γ confer pro- and anti-inflammatory properties to peritoneal macrophages in aged mice - Liscovsky, Miriam Veronica (2011)
Aging is accompanied by a disturbance in the homeostasis of the immune system. However, research into the behavior of macrophages in aging has shown disagreements about the functional status of these cells in aged mice. In this work, we studied the influence of aging on macrophage functions by evaluating the pro- and anti-inflammatory parameters of peritoneal macrophages preserved in their natural microenvironment. Resident peritoneal macrophages from old mice, in the context of their natural milieu, were found to respond with a similar phenotype and functional pattern to macrophages from young mice. In addition, we evaluated the macrophage response to CpG-ODN, a well-known Th1 promoter. CpG-ODN + IFN-γ were able to activate not only nitric oxide to initiate the inflammatory response, but also IL-12 in resident and inflammatory peritoneal macrophages from aged mice in the context of their natural milieu, although some quantitative differences were found in IL-10 and IL-12 secretion. With this stimulus, NO secretion and arginase activation were maintained in peritoneal macrophages during aging. These results will help to elucidate potential immunization strategies with CpG-ODN in the elderly.